The Role of Brand Awareness and Integrated Marketing Communication on Consumer Purchase Decision of Online Travel Consumers - Sukirman Sukirman; Yunidyawati Azlina; Tengku Kespandiar; Teguh Setiawan Wibowo; Umi Setyorini (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this research is to explore and assess the deployment of integrated marketing communications in order to increase brand recognition and its impact on purchase decisions. Purposive sampling was utilized in this work as a non-probability sampling strategy. The researchers considered numerous sample characteristics in this study, including age (17-50) and having utilized travel agency services at least once to book aircraft tickets, trains, events, or hotel reservations. The purposive sampling technique was applied, and 100 samples were collected. SmartPLS was utilized to do partial least squares analysis. According to the findings of the study, integrated marketing communication has a direct effect on brand awareness; integrated marketing communication has a direct effect on purchasing decisions; brand awareness has a direct effect on purchase decisions; and integrated marketing communication influences purchase decisions indirectly through brand awareness.